2004
DOI: 10.1142/s0218271804004773
|View full text |Cite
|
Sign up to set email alerts
|

A New Analysis of the Medium-Timescale Periodicity in S5 0716+714

Abstract: In this paper, we have collected the available observation data of BL Lac S5 0716+714 in I-band from published literature during 1994 to 2000. The light curve shows S5 0716+714 is very active and very complicated non-sinusoidal variations. We studied its mediumtimescale periodicity using the Jurkevich and power spectrum method to search for the possible medium-timescale periods and found that one possible medium-timescale periodic with a period of around 14±0.1 day is obtained for S5 0716+714. It is interestin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 30 publications
0
5
1
Order By: Relevance
“…This is also agreement with the timescale P γ = 344.0 ± 16.4 days obtained by us. However, there are no obvious signs of 1-7, 4, 10, 14, 24 days, 3.3 and 5.5-6 years period in our results (Quirrenbach et al 1991;Qian et al 2002;Ma et al 2004;Raiteri et al 2003;Yuan et al 2017). For the timescale of 3.3 and 5.5-6 years obtained by Raiteri et al (2003), the duration of the data train used in the paper is too short to confirm them (Kidger et al 1992).…”
Section: Discussioncontrasting
confidence: 43%
See 2 more Smart Citations
“…This is also agreement with the timescale P γ = 344.0 ± 16.4 days obtained by us. However, there are no obvious signs of 1-7, 4, 10, 14, 24 days, 3.3 and 5.5-6 years period in our results (Quirrenbach et al 1991;Qian et al 2002;Ma et al 2004;Raiteri et al 2003;Yuan et al 2017). For the timescale of 3.3 and 5.5-6 years obtained by Raiteri et al (2003), the duration of the data train used in the paper is too short to confirm them (Kidger et al 1992).…”
Section: Discussioncontrasting
confidence: 43%
“…The foregoing analysis suggests that there is a tentative variability periodicity on timescale P 15GHz = 266.0 ± 11.5 and P γ = 344.0 ± 16.4 days in the radio 15 GHz, and γ-ray datasets of S5 0716+714, respectively. The variability of S5 0716+714 was studied in many literatures (Quirrenbach et al 1991;Qian et al 2002;Ma et al 2004;Rani et al 2013;Wiita et al 2009;Liao et al 2014;Raiteri et al 2003). They found that there are various timescales from 1 days to several years in the light curves of the object.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Observations also show that some sources exhibit medium-time scale variability on time scales of weeks or months. Impey et al (2000) claimed that PKS 0716+714 likely has a periodic variation on time scales of about 10 days and Ma et al (2004) found that PKS 0716+714 has a variability period of 14 ± 0.1 days by using Jurkevich's method (1971a) and power spectrum analysis. Lainela et al (1999) and Katajainen et al (2000) have obtained a variability period about 65 days for 3C 66A and Xie et al (2002a) also found that 3C 66A has a variability period of 63 ± 5 days.…”
Section: Introductionmentioning
confidence: 99%
“…Qian et al also found evidence of quasi-periodic oscillations in their observations, and there may be a period on the order of 10 days in its light curve [24]. Ma et al obtained one possible medium-timescale variation with a period of around 14 days [25]. Raiteri et al found there may be an oscillation on a 3.3 year time scale in the R band light curve [26].…”
Section: Introductionmentioning
confidence: 94%